2019
DOI: 10.1002/jrs.5724
|View full text |Cite
|
Sign up to set email alerts
|

Cover Image

Abstract: The cover image is based on the Research Article Raman band widths of anhydrite II reveal the burning history of high‐fired medieval gypsum mortars by Thomas Schmid et al., https://doi.org/10.1002/jrs.5632.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…They were able to fill the gaps in the literature and give the correct identification of aphthitalite and thenardite even when secondary bands were not observed. Schmid et al [133] found that the Raman band widths of anhydrite II reveal the burning history of high-fired medieval gypsum mortars. Sodo et al [134] employed Raman and time of flight secondary ion mass spectrometry to answers specific conservation questions regarding Bosch painting of Saint Wilgefortis Triptych.…”
Section: Frescos Mortars Paintings Including Wall and Rock Paintimentioning
confidence: 99%
“…They were able to fill the gaps in the literature and give the correct identification of aphthitalite and thenardite even when secondary bands were not observed. Schmid et al [133] found that the Raman band widths of anhydrite II reveal the burning history of high-fired medieval gypsum mortars. Sodo et al [134] employed Raman and time of flight secondary ion mass spectrometry to answers specific conservation questions regarding Bosch painting of Saint Wilgefortis Triptych.…”
Section: Frescos Mortars Paintings Including Wall and Rock Paintimentioning
confidence: 99%
“…In the predecessor paper to this article, we described a red luminescence emission consisting of several sharp lines (thus, in some other studies confused with Raman bands), which within the phases of the lime cycle was assigned to burnt lime (calcium oxide, CaO), because the effect was lost upon slaking to calcium hydroxide and not restored during carbonation to calcium carbonate. [1] Due to its specificity, this luminescence effect was employed for mapping the distribution of Raman-inactive free lime CaO in the microspectroscopic imaging of a 19th-century Portland cement mortar sample, [2] but the reason for the emission was not known so far. A literature survey yields foreign element ions, fluorescing point defects (F centres) and radical ions (e.g., O -• ) in the crystal lattice as possible reasons.…”
Section: Introductionmentioning
confidence: 99%
“…A literature survey yields foreign element ions, fluorescing point defects (F centres) and radical ions (e.g., O -• ) in the crystal lattice as possible reasons. [1] Because often, rare earth (f-block) elements are mentioned in the discussion of luminescence in inorganic phases, we would like to emphasise the possibility of dblock element ions in a crystal field as potential reason and give the Raman community a better understanding of the according theoretical background. In our predecessor study, rare earth element ions were considered unlikely as fluorophores, because of the reproducibility of the observed spectral pattern requiring that always the same of these easily interchangeable elements would have to be present in CaO.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations